2001
DOI: 10.1016/s0091-3057(01)00563-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency decreases dopamine D1 and D2 receptors in rat brain

Abstract: Iron deficiency (ID) in early life is known to alter neurological development and functioning, but data regarding specific effects on dopamine biology are lacking. The objective of this study was to determine the extent of functional alterations in dopamine receptors in two dopaminergic tracts in young, growing, iron-deficient rats. Forty male and 40 female weanling Sprague-Dawley rats were fed either an iron-deficient (ID) diet or control (CN) diet for 6 weeks. ID decreased densities of D(1) and D(2) receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
182
3
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(200 citation statements)
references
References 32 publications
13
182
3
2
Order By: Relevance
“…[23][24][25] The effects of iron deficiency on fatigue can be explained by decreased activity of irondependent enzymes; for example, those affecting the metabolism of neurotransmitters that enhance neurophysiologic changes. [26][27][28][29] However, we presume that such physiologic changes could be confused with depression or anxiety; thus, the effect of iron supplementation on mood disor-…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] The effects of iron deficiency on fatigue can be explained by decreased activity of irondependent enzymes; for example, those affecting the metabolism of neurotransmitters that enhance neurophysiologic changes. [26][27][28][29] However, we presume that such physiologic changes could be confused with depression or anxiety; thus, the effect of iron supplementation on mood disor-…”
Section: Discussionmentioning
confidence: 99%
“…Among these, surprisingly, memory disorders appeared as significantly less frequent in women with serum ferritin concentrations below 15 mg/l, or even more so, below 10 mg/l. Others demonstrated that, in rodents, iron deficiency without anemia protected against the neurodegeneration of specific cerebral zones, in particular, the hippocampus zone (Hallberg & Asp, 1996), one of the memory zones (Bohbot et al, 2000), whereas subjects with iron-deficient anemia presented more frequently with memory loss because of major alterations of enzymatic reactions of the serotonin metabolism (mitochondrial aldehyde oxidase) or of catecholamines catabolism (mitochondrial monoamine oxidase) within the neuronal mitochondria, leading to a cerebral storage of triptaminergic derivatives and of catecholamines (adrenaline, noradrenaline and dopamine) (Youdim et al, 1983(Youdim et al, , 1989Hallberg & Asp, 1996;Youdim & Yehuda, 2000;Erikson et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action by which iron deficiency causes to neurocognitive disorders is not fully understood. In some studies, it was shown that ID decreased expression of dopamin receptors, disrupted myelinization or disrupted the function of various enzymes involved in the nerve tissue (17)(18)(19). Again, another important yet controversial clinical effect of iron deficieny is its effects on the immune system (20)(21)(22).…”
Section: Clinical Findingsmentioning
confidence: 99%